Experimental and numerical simulation analysis of R-290 air conditioner leak. (June 2018) - Maojuan, Hu; Jinbo, Li; Zhe, Liu; Tingxun, Li
Highlights: A three dimensions CFD was developed to simulate refrigerant leak within RAC. The effects of parameters like airflow were measured and analyzed in detail. The airflow volume with speed margin of 0.2 m/s was used to assess airflow effect. The jet camber resulted from refrigerant and Coanda flow were illustrated clearly. Abstract: Different mass R-290 (propane) leaked into the room from the inside and outside of a split type air conditioner indoor unit, and the refrigerant concentration was measured by infrared gas sensors. A CFD mode for RAC indoor unit including heat exchanger and fan was developed and verified by the test data. Through experiment and simulation, the dispersion characteristics of the refrigerant under different conditions were studied. The influence of installation height, leak point location, airflow rate and angle were tested and analyzed. Using velocity and concentration contours, jet camber resulted from leaked refrigerant and Coanda flow were illustrated clearly. The airflow volume at speed greater than 0.2 m/s could be applied directly to assess the effect of airflow on refrigerant mixing and diffusion.